The Effect of Enrichment of Water fleas with Viterna on the Survival and Growth of Koi Fish Larvae (Cyprinus carpio) - Nia Vitaloka; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted from January to February 2019 at the Laboratory of Fish Hatchery and Breeding at the Faculty of Fisheries and Marine Sciences, University of Riau. This study aims to determine the viterna soaking dose in enriching water lice. The method used is a one-factor Completely Randomized Design (CRD) and three treatments with three replications. The treatment was carried out 3 replications to obtain 12 experimental units. The treatment in this study was D0 = Dose 0 (Control), D40 = 5 hours with a dose of 40 ml / l, D50 = 5 hours with a dose of 50 ml / l and D60 = 5 hours with a dose of 60 ml / l. The results showed that Daphnia sp enrichment had a significant effect (P <0.05) on the growth of koi fish larvae, namely the dose of viterna 50 ml / l of water, resulting in absolute weight growth of 0.43 g, specific growth rate of 6.13% / day, absolute length growth of 2.98 cm, highest survival at a dose of 40 ml / l which is equal to 91.67% and the highest color quality at a dose of 50 ml / l. The water quality parameter values obtained during the study showed a good range for the growth of koi fish larvae, namely temperatures ranging from 27.0 to 31ºC and pH 5-6.5 Keywords :Water fleas, Viterna, Growth, Survival, cyprinus carpio